2010
DOI: 10.1007/s11205-010-9716-2
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Sense of Belonging to the Home Town: The Role of Residential Mobility

Abstract: Place identity, Sense of community, University students,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Numerous studies have used these theoretical perspectives to understand students' choice of higher education study location and their transition from home to university (see e.g. Chow & Healey, 2008;Cicognani et al, 2011;Gabriel, 2006;Holton, 2015). In these studies, the focus is on students' perceptions and feelings with regards to place and belonging.…”
Section: Students' Choice Of Higher Education Institutionmentioning
confidence: 99%
“…Numerous studies have used these theoretical perspectives to understand students' choice of higher education study location and their transition from home to university (see e.g. Chow & Healey, 2008;Cicognani et al, 2011;Gabriel, 2006;Holton, 2015). In these studies, the focus is on students' perceptions and feelings with regards to place and belonging.…”
Section: Students' Choice Of Higher Education Institutionmentioning
confidence: 99%
“…Simply because students may have grown up in the community within which they attend college does not mean that their sense of community with that locality cannot increase. Cicognani, Menezes, and Nata (2011) found that students who were native to their college's location experienced an increase in sense of community from freshman to senior year, indicating that they had not reached their peak level of sense of community within their home locality just by growing up in that community. In other words, there is always room for growth.…”
Section: Transiency and The Local Studentmentioning
confidence: 99%
“…Promoting students' belongingness is imperative in the Chinese city of Hong Kong, where the study takes place, as well as other societies (Barrett, 2007;Cicognani et al, 2011;Tse, 2007). Most notable is the expanding of mass education that draws myriad resources and people to the provision and reception of education (Kember, 2010;Post, 2003).…”
mentioning
confidence: 99%